Preparation and Evaluation of Telmisartan Solid Dispersion as Sublingual Tablets - Aziz, Hiba A.; Al-Akkam, Entidhar J. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Telmisartan is an antihypertensive angiotensin II receptor antagonist drug commonly used to treat hypertension and renal disease. Based on the Biopharmaceutical Classification System, it’s a Class II poorly soluble drug. Objective: To prepare a sublingual tablet by increasing the dissolution and solubility of Telmisartan utilising the solid dispersion method. Methods: Three methods were obtained to prepare the solid dispersion of telmisartan: solvent evaporation, kneading, and microwave method. Each method uses soluplus as a hydrophilic carrier in different ratios of 1%, 2%, and 3%. Preparation of ternary solid dispersion by adding potassium carbonate salt to the binary solid dispersion. After that, the preparation of the sublingual tablets was done by applying a direct compression method, using different types and ratios of super disintegrants such as crospovidone, croscarmellose, and sodium starch glycolate in 5% and 10%. Study the evaluation tests of sublingual tablets, such as friability, hardness, disintegration time, and dissolution time. Results: The solid dispersion showed an improvement in solubility over the pure medication. The best result was obtained with the formula (Telmisartan, Soluplus, and K2CO3 salt at a 1:1:0.3 ratio) prepared by the microwave method. In this method and the high ratio of soluplus, the solubility increased more than in the solvent evaporation and kneading methods. The selected tablet is prepared using crospovidone 10% as a super disintegrant that appears disintegration time in 5 seconds and releases in 1 min in dissolution media. Conclusion: The solubility and dissolution of Telmisartan were improved by microwave-based ternary solid dispersion using hydrophilic carriers and salt in a ratio of 1:1:0.3 (drug: carrier: salt). The analysis exerts the increases in wettability, enhanced solubility, and dissolution due to conversion from crystal to amorphous state.